Inhibition of Bruton's TK regulates macrophage NF‐κB and NLRP3 inflammasome activation in metabolic inflammation. (26th August 2020) - Purvis, Gareth S.D.; Collino, Massimo; Aranda‐Tavio, Haidee; Chiazza, Fausto; O'Riordan, Caroline E.; Zeboudj, Lynda; Mohammad, Shireen; Collotta, Debora; Verta, Roberta; Guisot, Nicolas E.S.; Bunyard, Peter; Yaqoob, Magdi M.; et al.
Abstract : Background and Purpose: There are no medications currently available to treat metabolic inflammation. Bruton's tyrosine kinase (BTK) is highly expressed in monocytes and macrophages and regulates NF‐κB and NLRP3 inflammasome activity; both propagate metabolic inflammation in diet‐induced obesity. Experimental Approach: Using an in vivo model of chronic inflammation, high‐fat diet (HFD) feeding, in male C57BL/6J mice and in vitro assays in primary murine and human macrophages, we investigated if ibrutinib, an FDA approved BTK inhibitor, may represent a novel anti‐inflammatory medication to treat metabolic inflammation. Key Results: HFD‐feeding was associated with increased BTK expression and activation, which was significantly correlated with monocyte/macrophage accumulation in the liver, adipose tissue, and kidney. Ibrutinib treatment to HFD‐fed mice inhibited the activation of BTK and reduced monocyte/macrophage recruitment to the liver, adipose tissue, and kidney. Ibrutinib treatment to HFD‐fed mice decreased the activation of NF‐κB and the NLRP3 inflammasome. As a result, ibrutinib treated mice fed HFD had improved glycaemic control through restored signalling by the IRS‐1/Akt/GSK‐3β pathway, protecting mice against the development of hepatosteatosis and proteinuria. We show that BTK regulates NF‐κB and the NLRP3 inflammasome specifically in primary murine and human macrophages, the in vivo cellular target of ibrutinib. Conclusion and Implications: We provide "proof of concept" evidence that BTK is a novel therapeutic target for the treatment of diet‐induced metabolic inflammation and ibrutinib may be a candidate for drug repurposing as an anti‐inflammatory agent for the treatment of metabolic inflammation in T2D and microvascular disease. Abstract :